Trends and Recommendation Practices in Didactical Design for Mathematics Learning: A Systematic Literature Review - Juhaevah, Fahruh; Upu, Hamzah; Bernard; Talib, Ahmad (Kirana Publisher (KNPub), 2025)
This systematic literature review examines didactical design in mathematics learning from 2015-2025, analyzing implementation patterns across educational contexts while evaluating key design elements. Following PRISMA guidelines, we analyzed 32 articles from diverse international sources. Results revealed distinct educational level-specific approaches to mathematics instruction, with geometry emerging as the predominant content area. Findings indicate that successful didactical designs align instructional approaches with students’ developmental stages: gamification for elementary arithmetic, Realistic Mathematics Education for junior high geometry, problem-based learning for senior high trigonometry, and Socratic questioning for undergraduate calculus. GeoGebra was identified as the most frequently utilized educational tool, highlighting the significance of dynamic mathematics software. This study contributes to mathematics education by providing evidence-based guidance for didactical design implementation while identifying critical research gaps regarding cross-cultural effectiveness, longitudinal impacts, and technology integration. The geographical concentration of studies suggests a need for more diverse international perspectives to strengthen the generalizability of findings.